Approximation Theorems for Functions of Two Variables via σ-Convergence. (10th February 2014) - Alghamdi, Mohammed A.
Abstract : Çakan et al. (2006) introduced the concept ofσ -convergence for double sequences. In this work, we use this notion to prove the Korovkin-type approximation theorem for functions of two variables by using the test functions 1, x, y, andx 2 + y 2 and construct an example by considering the Bernstein polynomials of two variables in support of our main result.